Anomalous winter moisture transport associated with the recent surface warming over the Barents–Kara seas region since the mid‐2000s. (25th October 2019) - Wang, Sai; Chen, Wen; Chen, Shangfeng; Nath, Debashis; Wang, Lin
Abstract: Observational evidences have shown that the increased water vapour and accompanying enhancement of downward infrared radiation (IR) can explain the abrupt warming of surface air temperature (SAT) over the Barents–Kara Seas during boreal winter. This study investigates anomalous moisture transport associated with the abrupt change of SAT since the mid‐2000s over the Barents–Kara Seas, since moisture transport contributes to the anomalous water vapour and downward IR. Results show that anomalous stationary moisture flux induces anomalous moisture convergence over the Barents–Kara Seas region, whereas the anomalous transient flux opposes the anomalous moisture convergence there. Hence, the anomalous stationary moisture transport is suggested to be responsible to the increased water vapour over the Barents–Kara Seas region. Further decomposition of the stationary moisture flux indicates that the anomalous moisture convergence associated with the change in atmospheric mean flow plays an important role in the increased water vapour on both interannual and decadal time scales. In addition, decrease in the synoptic‐scale eddy activity observed over northern Siberia may contribute to generation of the anomalous atmospheric mean flow via eddy feedback processes. Abstract : The normalized time series of winter (a) SAT, (b) downward IR and (c) TCW averaged over the Barents–Kara seas region (72.5°–85 o N, 0°–75°E) for the period 1979–2017. Lepage tests (with 9‐year running window) of the normalized time series of winter (d) SAT, (e) downward IR and (f) TCW averaged over Barents–Kara seas region. The red (blue) line indicates the Lepage test is significant at the 99% (95%) confidence level. Differences in the winter (g) SAT (units: K), (h) downward IR (units: W·m −2 ) and (i) TCW (units: kg·m −2 ) between 2004–2017 and 1979–2003. The dotted areas in (g)–(i) denote the differences that are significantly different from zero at the 95% confidence level